2015
DOI: 10.1111/pbi.12496
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide‐directed mutagenesis for precision gene editing

Abstract: SummaryDifferences in gene sequences, many of which are single nucleotide polymorphisms, underlie some of the most important traits in plants. With humanity facing significant challenges to increase global agricultural productivity, there is an urgent need to accelerate the development of these traits in plants. oligonucleotide‐directed mutagenesis (ODM), one of the many tools of Cibus’ Rapid Trait Development System (RTDS ™) technology, offers a rapid, precise and non‐transgenic breeding alternative for trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 60 publications
0
81
1
2
Order By: Relevance
“…The synthetic oligo's consist of both DNA and modified nucleotides or other end-protective chemistries. These modifications prevent the oligonucleotides from undergoing recombination (i.e., being incorporated into the genome), while maintaining the ability to act as a mutagen (Sauer et al 2016). Once the correction process is completed, the oligos are degraded.…”
Section: Methods Description and List Of Techniquesmentioning
confidence: 99%
“…The synthetic oligo's consist of both DNA and modified nucleotides or other end-protective chemistries. These modifications prevent the oligonucleotides from undergoing recombination (i.e., being incorporated into the genome), while maintaining the ability to act as a mutagen (Sauer et al 2016). Once the correction process is completed, the oligos are degraded.…”
Section: Methods Description and List Of Techniquesmentioning
confidence: 99%
“…TALE proteins consist of a central domain responsible for DNA binding, nuclear localization crRNA, Cas9 proteins Kumar and Jain [6] Sauer et al [7] 2015 2016…”
Section: Transcription Activator-like Effector Nucleases (Talens)mentioning
confidence: 99%
“…Noman et al [12] 2016 Sauer et al [7] 2016 signal, and a domain that serves as activator of transcription of the target gene (Table 1) [54]. For the first time, the DNAbinding ability of these proteins was described in 2007 [55], and a year later, two scientific groups have decoded the recognition code of target DNA sequence by TALE proteins [56].…”
Section: Transcription Activator-like Effector Nucleases (Talens)mentioning
confidence: 99%
“…As an additional option, synthetic chimeric RNA/DNA molecules or single-stranded DNA oligonucleotides (SDOs) can be employed as vectors to produce oligonucleotide-targeted nucleotide exchange (OTNE) at a specific site of plant genomic DNA (Breyer et al 2009;Sauer et al 2016a;Sauer et al 2016b). The pioneering studies preferentially used chimeric RNA/DNA oligonucleotides for the induction of gene-specific mutations (Beetham et al 1999;Kochevenko and Willmitzer 2003;Okuzaki and Toriyama 2004;Ruiter et al 2003;Zhu et al 2000;Zhu et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Out of several parameters, the optimal length and structure of oligonucleotide molecules need to be determined for a given organism. Sauer et al (2016a) reported that oligonucleotide length had a positive correlation with the frequency of targeted edits as monitored by changing the blue fluorescent protein to green fluorescent protein. Dong et al (2006) developed a transient assay system based on cobombardment of mutated GFP plasmid constructs with targeting SDO GFP to the scutellum cells of immature wheat embryos.…”
Section: Introductionmentioning
confidence: 99%